Site Specific Nutrient Management for Maize on Ultisols Lampung - Murni, Andarias Makka; Pasuquin, Julie Mae; Witt, Christian (UNIVERSITY OF LAMPUNG, 2010)
Site Specific Nutrient Management for Maize on Ultisols Lampung (A M Murni, JM Pasuquin, and C Witt): Lampung is the third major maize producing province in Indonesia after East Java and Central Java. In Lampung maize is cultivated mainly in upland areas with ultisols and only some cultivated on paddy field as a secondary crop in the dry season. The average maize yield in Lampung is still 3.4 Mg ha-1 bellow yield potential of 7-10 Mg ha-1. To increase the productivity of maize through site-specific nutrient management (SSNM), on-farm trials were conducted in five locations in Lampung i.e. four locations in Central Lampung District (Sidowaras, Binjai Ngagung, Watu Agung and Balai Rejo) and one location in South Lampung District (Trimulyo, Tegineneng Sub District) during the 2004/2005, 2005/2006 and 2006/2007 rainy seasons. The experimental setup followed a standard protocol at all sites and included nutrient omission plots (PK, NK, NP) to estimate indigenous nutrient supplies, an NPK plot to measure yield response to fertilizer application, and a farmers’ fertilizer practice (FFP) plot in each farmer’s field. An SSNM treatment plot was included in the second and third seasons. Each of the above treatments was paralleled by a plot with improved crop management practice (ICM), i.e. higher planting density, addition of lime, and addition of magnesium. Results showed that yield response to fertilizer N, P and K application in these sites were: N = 2.3-4.1 Mg ha-1; P = 0.6-2.0 Mg ha-1; K = 0.3-2.4 Mg ha-1. Attainable yield in the three seasons on average ranged from 7.6 Mg ha-1 to 10.6 Mg ha-1. Yield in the SSNM treatment (with or without ICM) was significantly higher than the FFP indicating great opportunities for farmers to increase productivity and profitability with improved nutrient and crop management.